Free yet? Progress, setbacks, tensions and the potential futures of South Africa’s free higher education policy: A 6 year "WPR" critical review - Masutha, M.; Motala, S. (South African Journal of Higher Education, 2023)
Prior to 2017, maladministration, unfunded and underfunded students, misalignment with student needs, high non-completion rates and a violent student debt crisis characterised South Africa’s student financial aid scheme, and triggered annual unrest across the higher education (HE) sector. Following a wave of protests by the #FeesMustFall movement and widespread calls for a free decolonised HE, in 2017, the South African government replaced its 26 year old income-contingent student loan scheme with a grant-based free HE education policy for poor and working-class students. While the policy intervention restored relative stability across the sector, several fault lines in the student funding policy remain. In this article, drawing on a combination of qualitative policy document analysis and descriptive statistics, we employ Carol Bacchi “what’s the problem represented to be?” (WPR) approach to analyse recent student funding policy developments in South African HE. We employ the WPR approach to (a) direct attention to the significance of reflecting on how the HE student funding problem has been constituted and framed in policy proposals, and (b) challenge the dominant “problem solving” paradigm (inherent in mainstream policy propositions) by drawing attention to benefits of an alternative “problem-questioning” approach to the country’s pursuit for a just and equitable student funding model. We then make some recommendations on how South African HE policymakers can avoid the pitfalls of well-meaning HE funding policies turning into instruments for creating and reproducing the very disparities they are meant to ameliorate.